GSK114: A selective inhibitor for elucidating the biological role of TNNI3K. Issue 14 (15th July 2016) - Lawhorn, Brian G.; Philp, Joanne; Graves, Alan P.; Shewchuk, Lisa; Holt, Dennis A.; Gatto, Gregory J.; Kallander, Lara S.
Graphical abstract: Abstract: A series of selective TNNI3K inhibitors were developed by modifying the hinge-binding heterocycle of a previously reported dual TNNI3K/B-Raf inhibitor. The resulting quinazoline-containing compounds exhibit a large preference (up to 250-fold) for binding to TNNI3K versus B-Raf, are useful probes for elucidating the biological pathways associated with TNNI3K, and are leads for discovering novel cardiac medicines. GSK114 emerged as a leading inhibitor, displaying significant bias (40-fold) for TNNI3K over B-Raf, exceptional broad spectrum kinase selectivity, and adequate oral exposure to enable its use in cellular and in vivo studies.